Cooperativas como política pública: Electrificación rural en Chile, 1940-1970. - Tomás Labarca, José (European Review of Latin American & Caribbean Studies, 2016)
This article examines the relations between cooperatives and the State in Chile during the implementation of the National Electrification Plan from 1940 to 1970. Scholars generally agree that Latin American developmentalism entailed State expansion and market regression. I challenge this common explanation by arguing that in rural areas the Electrification Plan was carried out largely by cooperatives. This in turn prompted the creation of a State bureaucracy charged with controlling the electrification cooperatives, and helped to develop technical expertise and more efficient economic administration. Based on these findings, the article suggests that coordination between the State and the cooperatives led to technical relations and not, as it is often argued, one of co-optation. Furthermore, state expansion allowed for the creation of a new cooperative market. In conclusion, electrification cooperatives triggered economic and institutional innovations that raise new questions on how to explain Latin American, developmental strategies.